Design and development of an SLA service management system for a rapid prototyping competency unit - Lin, Liutong. (2008)
This dissertation describes the design and implementation of a management system for one of the Rapid Prototyping machines in the Rapid Prototyping Competency Unit of the Engineering School at Temasek Polytechnic.